2003
DOI: 10.1590/s0034-72992003000100013
|View full text |Cite
|
Sign up to set email alerts
|

Da eletrococleografia transtimpânica em pacientes com e sem hydrops endolinfático e limiares auditivos iguais ou maiores que 50 decibéis

Abstract: ARTIGO ORIGINAL Rev Bras Otorrinolaringol. V.69, n.1, 74-82, jan./fev. 2003 « « Palavras-chave: eletrococleografia, perda auditiva, doença de Menière.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 16 publications
(18 reference statements)
0
10
0
3
Order By: Relevance
“…Munhoz (2001) 15 noticed that the value of 35% for PS/PA ratio in patients with hearing thresholds d•50dB corresponded to a rate of 100% of sensitivity and specificity to characterize endolymphatic hydrops. Soares et al (2003) 21 , however, upon studying patients with auditory thresholds e•50dB, observed that electrocochleography has less sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Munhoz (2001) 15 noticed that the value of 35% for PS/PA ratio in patients with hearing thresholds d•50dB corresponded to a rate of 100% of sensitivity and specificity to characterize endolymphatic hydrops. Soares et al (2003) 21 , however, upon studying patients with auditory thresholds e•50dB, observed that electrocochleography has less sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Munhoz (2001) 15 noticed that the value of 35% for PS/PA ratio in patients with hearing thresholds d•50dB corresponded to a rate of 100% of sensitivity and specificity to characterize endolymphatic hydrops. Soares et al (2003) 21 , however, upon studying patients with auditory thresholds e•50dB, observed that electrocochleography has less sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…These authors found that SP/AP ratio was the most sensitive and specific parameter for the identification of patients with endolymphatic hydrops. 16 Comparing results from transtympanic versus extratympanic electrocochleography in 20 patients with Ménière's disease and 20 control patients, Ghosh et al reported a significant difference in SP/AP ratio between cases and controls. For a value of SP/AP = 0.29, these authors found a sensitivity of 100% and specificity of 90% for transtympanic and 90% and 80% for extratympanic electrocochleography, respectively, concluding that extratympanic electrocochleography is an effective, easily implemented in clinical practice, and non-invasive method, when compared to the transtympanic method.…”
Section: Discussionmentioning
confidence: 99%
“…16,25,26 Lopes and Devaiah reported an increase in sensitivity of the test for diagnosis with the association of SP/AP ratio with the area under of the curve of SP/AP. 14,24 The SP/AP thresholds are variable in the literature, with diagnosis for values greater than 0.5, according to most authors searched.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation